Ununited Anconeal Process in the Dog. Pathogenesis and Treatment by Osteotomy of the Ulna - Sjöström, L.; Kasström, H.; Källberg, M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Several hypotheses regarding the pathogenesis of Ununited Anconeal Process (UAP) have been proposed. One theory argues that the condition is caused by an incongruous growth of the radius relative to the ulna, causing proximal displacement of the radial head and subsequent abnormal pressure on the anconeal process. By comparing the radiographic outline of elbow joints with unilateral UAP with the outline of contralateral elbows, evidence in support of this theory is reported.In accordance with the suggested pathogenesis of UAP, patients were treated surgically by osteotomy of the ulna to relieve pressure on the anconeal process and thus allow it to unite with the ulnar metaphysis. Results of surgery in 22 elbow joints in 20 dogs are reported; 21 UAPs united. In six cases a narrow radiolucent line remained between the anconeal process and the ulnar metaphysis, but judging from clinical performance and absence of secondary changes the anconeal process was firmly united. Short and long-term functional, clinical and radiographic results compare favourably with results reported previously after surgical resection of the UAP.Ununited Anconeal Process (UAP) may be caused by an incongruous growth between the radius and the ulna, with proximal displacement of the radial head and a subsequent pressure on the anconeal process. Evidence in support of this theory is reported. Results, after ulnar osteotomy to relieve the pressure, compare favourably with results reported after surgical resection of the UAP.
Keywords: Ununited Anconeal Process; pathogenesis; incongruous growth; ulnar osteotomy